Indian Slavery: An Atlantic and Hemispheric Problem - Goetz, Rebecca Anne (History compass, 2016)
Indian slavery was ubiquitous in the Americas and in the Atlantic World. Though Indian slavery varied in its forms and in its destructiveness depending on both time and place, Indian slavery shaped the colonial world, and its deleterious effects continue into the present. The practice of Indian enslavement and the Indian slave trade bound the continents and their islands together - enslavement was constant, and a constant risk; it could affect native peoples in any place, and all the major European colonial powers participated in the Indian slave trade. This article reviews recent literature on Indian slavery in the Atlantic and hemispheric perspectives and suggests questions and problems for further research.